Sethusamudram Project : divergent perspectives - Nambiar, E. K. G.; Suryanarayan, V.; University of Calicut. Chair for Maritime Studies and Research (Calicut : Publication Division, University of Calicut, 2005)
Papers presented at a national seminar on Sethusamudram Project - divergent perspectives, on July 12, 2005, organized by Chair for Maritime Studies and Research, Centre for Indian Ocean Studies, University of Calicut.
Keywords: Sethusamudram Project -- Congresses; Canals -- Environmental aspects -- India -- Tamil Nadu -- Congresses; Canals -- Economic aspects -- India -- Tamil Nadu -- Congresses; Canals -- Social aspects -- India -- Tamil Nadu -- Congresses